Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more
Standard view
Full view
of .
0 of .
Results for:
P. 1
Activity: Negative Exponents – 2010 in Order

# Activity: Negative Exponents – 2010 in Order

Ratings: (0)|Views: 18 |Likes:
An activity to investigate negative exponents with a graphing calculator and exercises and notes on simplifying expressions involving negative exponents.
An activity to investigate negative exponents with a graphing calculator and exercises and notes on simplifying expressions involving negative exponents.

### Availability:

See more
See less

05/12/2014

pdf

text

original

Activity: Negative Exponents
– 2010
In order to complete this activity you will need a graphing calculator
Type each of the followingexpressions into your calculator and:
Write the result as a decimal
Convert the decimal to a fraction (press “Math” then 1 or choose “Frac”)
Write the problem and result as an equation.
1) Example:
(1/2)^(-1)
Decimal: 2
Fraction:21
Equation:
12
1
=21
2)
(2/3)^(-1)
3)
(5)^(-1)
4)
(3/2)^(-1)
5)
(1/2)^(-2)
6)
(2/3)^(-2)
7)
(3/2)^(-2)
Now do the same thing with some more complicated expressions
1) Example:
((2/3)/(4/5))^(-1)
Decimal: 1.2
Fraction:65
Equation:
2345
1
=65
2)
(1/(2/3))^(-1)
3)
(1/(3/5))^(-1)
4)
(2/(3/5))^(-1)
5)
(1/(2/3))^(-2)
6)
(1/(3/5))^(-2)
7)
(2/(3/5))^(-2)

Review the following exponent rules. Remember:
The negative exponent is the reciprocal of thepositive exponent
. Also,
a power in the numerator can be transfered into the denominator and viceversa by simply negating the sign of it’s exponent.
1
a
2
=
a
2
and
3
x
2
4
y
5
z
2
=
3
z
2
4
x
2
y
5
.Here are a few examples that may help as you work through the practice set.
34
2
=
43
2
=4
2
3
2
=169= 179Why is the result greater?4
2
=14
2
=116Could you do this without a calculator?5
m
2
=5
m
2
3
x
2
4=34
x
2
5
x
2
y
3
3
x
4
y
4
=5
x
6
3
y
7
5
x
2
y
3
3
x
4
y
4
2
=
3
x
4
y
4
5
x
2
y
3
2
=
3
y
7
5
x
6
2
=3
2
y
7
·
2
5
2
x
6
·
2
=9
y
14
25
x
12
5
x
2
y
3
3
x
4
y
4
2
=
5
x
6
3
y
7
2
=
3
y
7
5
x
6
2
=9
y
14
25
x
12
Same expression as above
Simplify each expression.1
3
x
2
2
53
x
3
3
3
x
3
y
5
5
xy
3
2
4
3
xy
15
x
5
y
8
5
3
xy
15
x
5
y
8
3
6
27
x
2
y
5
3
x
5
y
2
5